2016
DOI: 10.1111/jmft.12196
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination and Implementation Research in Marriage and Family Therapy: An Introduction and Call to the Field

Abstract: Despite the considerable resources allocated to research to promote public health, interventions capable of benefiting individuals and families are not finding their way into regular practice. An important avenue for addressing this problem is through dissemination and implementation (D&I) science, a burgeoning research area focusing on translating empirical knowledge into everyday practice. This article begins by suggesting ways in which MFTs are uniquely equipped to contribute to and benefit from D&I researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…Marriage and family therapies are in a unique position to contribute to and benefit from dissemination initiatives (e.g., Withers, Reynolds, Reed, & Holtrop, 2017). An ideal location to begin the dissemination of findings from clinical research is at professional meetings.…”
Section: Transforming the Goals Of The Aamftmentioning
confidence: 99%
See 2 more Smart Citations
“…Marriage and family therapies are in a unique position to contribute to and benefit from dissemination initiatives (e.g., Withers, Reynolds, Reed, & Holtrop, 2017). An ideal location to begin the dissemination of findings from clinical research is at professional meetings.…”
Section: Transforming the Goals Of The Aamftmentioning
confidence: 99%
“…The train‐the‐trainer approach has been effective in other efforts to train psychotherapy educators, but would require faculty buy‐in and financial support from institutions (Nakamura et al., ). In addition, doctoral educators could explore developing hybrid courses that combine students and faculty from multiple programs and allow them to receive training in an evidence‐based intervention from off‐site experts (Withers et al., ).…”
Section: Change At the Level Of System Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Another area of concern is the dissemination of research into clinical practice. Withers, Reynolds, Reed, and Holtrop () suggested further establishing the clinical effectiveness of systemic and relational approaches to bridge this gap. These concerns expressed by scholars have not been investigated in quite some time, thus it is essential to obtain a comprehensive view of the clinical effectiveness research being published in our discipline.…”
Section: The Push For Mft Clinical Effectiveness Researchmentioning
confidence: 99%
“…They are presented here in no specific order. Dissemination and Implementation Research in Marriage and Family Therapy: An Introduction and Call to the Field, by authors Mathew C. Withers, Jamila E. Reynolds, Kayla Reed, and Kendal Holtrop also received high praise. One member of the council indicated that this “ article is beautifully written, on a topic that is vital to the future of mental health care, and includes a clear model for next steps .” A second honorable mention went to Results of Gottman Method Couples Therapy with Gay and Lesbian Couples by authors Salvatore Garanzini, Alapaki Yee, John Gottman, Julie Gottman, Carrie Cole, Marisa Preciado, and Carolyn Jasculca.…”
Section: Article and Reviewers Of The Yearmentioning
confidence: 99%